2022
DOI: 10.1108/ijbpa-10-2021-0137
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the causes of construction delay on the perspective of organization-sectors involved in the construction industry of Bangladesh

Abstract: PurposeConstruction delay always causes massive damage to the advancing construction industries, which is no different in the case of Bangladeshi construction industries. This paper aims to investigate the major delay factors causing construction delays in public-funded, mixed and private-funded construction projects of Bangladesh. Also, it offers preventive suggestions from expert stakeholders to reduce the recurrence of delays.Design/methodology/approachAt first, an extensive literature review was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In Bangladesh, Assafi et al (2022) used the relative importance index method and recommended that manpower, materials, consultant, contractor, contract, external and client-related factors are the key risk factors. In Nepal, Gain et al (2022) employed the relative importance index and found that the amendments in regulations, weather situations, unexpected circumstances, variation orders, productivity, functionalities, poor organizational structure, poor drafting of contracts, poor site management, financial difficulties, labor shortage, inadequate construction methods, poor decision-making, inferior quality, material shortage and drawings issues are the main hazard concerns.…”
Section: Risk Factors In Asiamentioning
confidence: 99%
“…In Bangladesh, Assafi et al (2022) used the relative importance index method and recommended that manpower, materials, consultant, contractor, contract, external and client-related factors are the key risk factors. In Nepal, Gain et al (2022) employed the relative importance index and found that the amendments in regulations, weather situations, unexpected circumstances, variation orders, productivity, functionalities, poor organizational structure, poor drafting of contracts, poor site management, financial difficulties, labor shortage, inadequate construction methods, poor decision-making, inferior quality, material shortage and drawings issues are the main hazard concerns.…”
Section: Risk Factors In Asiamentioning
confidence: 99%
“…A project by [14] examined the causes of construction delays in Bangladeshi public, mixed, and privately funded building projects. The overall RII ranking of the 37 delay factors showed "Construction mistakes and defective work," "Contract modifications by the client," and "Adverse weather conditions" as the top three factors causing the delay.…”
Section: B Previous Related Studiesmentioning
confidence: 99%
“…Assafi M., et al [10] investigated the perspective of construction organizations in Bangladesh about the causes of delay. The RII was the tool adopted to evaluate these causes.…”
Section: Literature Reviewmentioning
confidence: 99%